On-chip coil integrated superconducting tunnel junction for a high performance X-ray detector - Taino, Tohru; Kikuchi, Katsuya; Nanme, Masaki; Nakagawa, Hiroshi; Aoyagi, Masahiro; Sato, Hiroshi; Akoh, Hiroshi; Maehata, Keisuke; Ishibashi, Kenji; Sato, Hiromi; Otani, Chiko; Ikeda, Tokihiro; et al. (Physica. C, Superconductivity, 2002)
On-chip coil integrated superconducting tunnel junction (OC 2-STJ) has been demonstrated for high performance X-ray detector. The STJ was fabricated by an improved fabrication technique based on a high quality Nb/Al/AlO x /Nb junction technology. The STJ shows high quality current–voltage characteristics with an ultra-low leakage current of a few nA at 0.4 K for 100 μm×100 μm junction. Typical critical current of the coil was achieved more than 50 mA for 2 μm line width, which can generate a magnetic field of about 10 mT into the STJ. It was found that the OC 2-STJ successfully responded to the irradiated 5.9 keV X-ray.